1991
DOI: 10.1007/bf00127125
|View full text |Cite
|
Sign up to set email alerts
|

A cost-benefit analysis of a third camera for stereo correspondence

Abstract: This paper looks at the twin issues of the gain in accuracy of stereo correspondence and the accompanying increase in computational cost due to the use of a third camera for stereo analysis. Trinocular stereo algorithms differ from binocular algorithms essentially in the epipolar constraint used in the local matching stage. The current literature does not provide any insight into the relative merits of binocular and trinocular stereo matching with the matching accuracy being verified against the ground truth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…4.80% for the corridor scene, and 2.98% for the office scene. The above dispanty errors compare very well with other reported result\ 1131- [15], [20]. For the cube images, all 72 pairs of lines are correctly matched, and the disparity errors occur mostly on the slanted edges in the cubes.…”
Section: Performance Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…4.80% for the corridor scene, and 2.98% for the office scene. The above dispanty errors compare very well with other reported result\ 1131- [15], [20]. For the cube images, all 72 pairs of lines are correctly matched, and the disparity errors occur mostly on the slanted edges in the cubes.…”
Section: Performance Analysissupporting
confidence: 89%
“…It is known that if the two cameras of a binocular system are displaced horizontally, then the horizontal lines in two images cannot be uniquely matched unless the end points of the horizontal lines can be located. A good solution to this is the use of three cameras as suggested by [13]- [15]. The trinocular stereo vision facilitates an additional powerful constraint, the trinocular uniqueness constraint [13], i.e., the horizontal and vertical disparities are identical, provided the camera displacements in both directions are equal.…”
Section: Introductionmentioning
confidence: 99%
“…The disparity of a point can be mathematically shown to be inversely proportional to the depth of the point . It can easily be shown that if the geometry of the system, the orientation and translational position between the two cameras, as well as the camera intrinsic calibration parameters are known then the coordinate position of a point can be mathematically determined [13].…”
Section: Texture Through Disparity (Stereovision)mentioning
confidence: 99%
“…Although systems with two cameras and one projector are more complicated, they are also more flexible. One of its advantages is the reduction of matching ambiguity [4][5][6] . Since there are two cameras in the system, the lightingto-image correspondence is not necessary and only image-to-image stereo matching is enough for calculating depths [7] .…”
Section: Introductionmentioning
confidence: 99%